The Relationship Between Stress and Eating Habits and the Occurence of GERD in Medical Students - Puspitasari, Aldayanti; Sukmagautama, Coana; Sari, Amelya Augusthina Ayu; Hermawati, Berty Denny (Smart Medical Journal, 2024)
Introduction: Gastro Esophageal Reflux Disease (GERD)is a disorder when food that has entered the stomach, goes back up into the esophagus or reflux, from several literature that has been read, in Indonesia many people experience this due to excessive stress, researchers develop existing research using the object and focus of research different. Research was conducted to determine the relationship between stress and eating patterns consisting of regular eating, consumption of spicy food, and consumption of fatty foods in UNS medical faculty students.Method: The research carried out was quantitative research with an observational analytical design and a cross-sectional approach. The research was conducted at the Faculty of Medicine, Universitas Sebelas Maret with a sample of 102 students, namely students from the Faculty of Medicine class 2020-2022. In collecting data, researchers used the GERD-Q questionnaire, the meal pattern questionnaire, FFQ and PSS. Followed by analyzing the data through editing, coding, scoring, tabulating, univariate, bivariate and multivariate analysis.Results: (1) There is a significant relationship between stressful conditions and the incidence of Gastroedophageal Reflux Disease (GERD) in UNS medical students; (2) there is a significant relationship between eating habits consisting of regular eating, consuming spicy food, consuming oily food and the incidence of Gastroedophageal Reflux Disease (GERD) in UNS medical students; (3) Based on a multivariate test, it was found that the most significant independent variable in the incidence of Gastroedophageal Reflux Disease (GERD) in UNS medical students was the habit of consuming oily/fatty foods which was 2 times faster in triggering the occurrence of GERD.Conclusion: From the discussion presented, it can be concluded that there is a significant relationship between stress and eating habits and the occurrence of GERD.